2008
DOI: 10.1111/j.1651-2227.2008.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc concentration in serum and cerebrospinal fluid simultaneously decrease in children with febrile seizure: Findings from a prospective study in Bangladesh

Abstract: Serum and CSF-Zn simultaneously decreased in FS children in comparison to their matched NSF peers. Further prospectively designed multicentral studies are recommended to conduct in geographically diverse regions involving larger sample to confirm or refute our findings. It remains crucial in standardizing/strengthening national seizure prevention protocol with adequate Zn supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
2
29
3
Order By: Relevance
“…In the current study, CSF to serum calcium ratio was low which may be explained by higher serum calcium level. The mean serum zinc level in our study was higher than other studies (11,13,19,23). The normal value for serum zinc level in our laboratory was considered 70 -200 μg/dL and no hypozincemia was detected.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In the current study, CSF to serum calcium ratio was low which may be explained by higher serum calcium level. The mean serum zinc level in our study was higher than other studies (11,13,19,23). The normal value for serum zinc level in our laboratory was considered 70 -200 μg/dL and no hypozincemia was detected.…”
Section: Discussioncontrasting
confidence: 51%
“…In some studies, CSF zinc levels in FS patients were significantly lower than control group (19)(20)(21)(22); whereas other studies revealed no significant difference in CSF zinc levels (14). Although, many investigations showed significantly lower level of serum zinc comparing to control group (12,19,22,23).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Clinical studies have also suggested an association between FSs and Zn 2+ levels. Mollah et al (16) reported that children with FSs had lower serum and CSF Zn 2+ levels compared to febrile children with no FSs. Seizuresensitive brain regions have high densities of zinc-containing neuronal terminals, and Zn 2+ plays well-known roles in transmission at glutamatergic, GABAergic, and glycinergic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zn 2+ deficiency parallels low GABA levels in cerebrospinal fluid (CSF), triggering seizures (8). Studies of the pathogenesis of febrile seizures (FSs), the most common type of seizure in children, found that Zn 2+ levels were low in both the serum and the CSF (16). The effect of Zn 2+ treatment in different experimental seizure models have been evaluated by Kumar H. et al (11).…”
Section: +mentioning
confidence: 99%